Implementation of assertive communication through leadership style and its implications for organisational commitment - Susanto, Heri; Sofyan, Ade (Trigin Publisher, 2024)
This study is intended to analyse the implementation of assertive communication in organisations to increase organisational commitment mediated by the implementation of leadership style. The purpose of this study is to determine how assertiveness in communication has influenced leadership style and has implications for organisational commitment. The results of the study obtained that assertive communication (X) has a direct influence on Organisational Commitment (Y) positively and significantly, which is 60.3%, and assertive communication on its mediating variable, namely leadership style (M) also has a positive and significant influence, which is 64.2%. While assertive communication implemented with leadership style has a positive and significant implication on organisational commitment, which is 74.2% where leadership style as mediation is declared to be able to mediate as evidenced by the decrease in the value of c which is 0.695 to 0.100